Management of Competitiveness in Hospitality Industry - Lyudmila Mikhailovna KORNILOVA; Anna Sergeevna KORNILOVA; Evgeniy Alekseevich IVANOV (Communications of International Proceedings, 2021)
The hospitality industry is one of the dynamically developing industries in the global economy. Review of literature and statistics indicates that this industry is also on the rise and becomes more and more in demand in our country. Therefore, the issues related to management of competitiveness of hotels and catering establishments are of particular relevance. In this article, we have analyzed the development of hotels and restaurants in Russia in recent years and identified the factors that contain the growth of their competitiveness and business activity.
Keywords: hotels; hospitality industry; restaurants; competitiveness; competitive advantages